Remaja Akhir Penggemar K-Pop: Celebrity Worship dan Self Concept (Universitas Muhammadiyah Metro, 2023)
The developing era and globalization have changed all aspects of life, including culture. Nowadays, foreign cultures are quickly affecting other cultures in the world due to globalization. One foreign culture which is loved by many people, especially teenagers in Indonesia, is the culture of South Korea. This study aims to discover how Celebrity Worship influences the Self-concept of late teen K-Pop fans. This study uses a quantitative research method with a correlational design and a sampling technique using purposive sampling, with the sample criteria being the late teens and K-pop fans. The data collection technique uses a questionnaire with data analysis using the Pearson Correlation Test. This study's results indicate a relationship between Celebrity Worship and the concept of 0.244%.